Environmental Education Policy Implementation in Botswana:The Role of Secondary Education Officers and School Heads - Mphemelang Ketlhoilwe (Environmental Association of Southern Africa, 2003)
The success of environmental education implementation depends on strong support from school authorities, educational planners, policy makers, administrators and others who are responsible for the education system. This paper is based on a study conducted among education officers and school heads at secondary school level in Botswana. It focuses on environmental education as practised by education officers and school heads. The results indicate some constraints regarding the logistics and official commitment of these key role players. The paper also puts forward some recommendations for further research and review of environmental education policy implementation, with a view to informing a more workable environmental education implementation strategy in Botswana.